Clinical Significance of Oligohydramnios in Patients with Preterm Premature Rupture of Membranes - O. M. Chistyakova; L. V. Gureeva; O. V. Radkov (Acta Biomedica Scientifica, 2021)
Background. Preterm premature rupture of membranes (PPROM) is one of the main causes of perinatal morbidity and mortality. Associated oligohydramnios may further exacerbate the condition leading to intra-amniotic inflammation and adverse obstetric and perinatal outcomes in preterm labor.Aim of the research. To determine an impact of oligohydramnios on patients with preterm premature rupture of membranes.Materials and methods. We performed a retrospective analysis of two groups of patients with PPROM: 56 patients with oligohydramnios were included in the main group, 111 patients without oligohydramnios were included in the control group. The gestational age varied from 24+0 weeks to 33+6 weeks. Amniotic fluid index, endocervical culture, leukogram and neutrophil-to-lymphocyte ratio (NLR), serum procalcitonin and C-reactive protein levels were assessed in all participants.Results. We witnessed a plethora of consequences in the group of women with PPROM and oligohydramnios: shorter latent phase, higher incidence of clinical chorioamnionitis, antenatal fetal distress, higher levels of C-reactive protein, leukocytes, neutrophils and NLR, lower level of lymphocytes, and increased growth of potentially pathogenic cervical flora. Moreover, the patients with oligohydramnios demonstrated a significantly higher rate of cesarean delivery. The combination of PPROM and oligohydramnios also take a toll on the condition of the newborns: they have lower 5-minute Apgar score and higher prevalence of respiratory distress syndrome, congenital pneumonia, and necrotizing enterocolitis. Furthermore, newborns from the main group are more likely to be admitted to the neonatal intensive care unit, compared with newborns from the control group.Conclusion. Oligohydramnios in PPROM is associated with a dramatic rise of numerous complications affecting both the women and the newborns.